The Theory of Evolution in contemporary culture. Biological evolution and cultural evolution [with english version] (Nóema, 2013)
The theory of  biological Evolution after the recent discoveries of molecular biology, immunology and embryology: the “adaptive mutation” discovery in bacteria and its reality in higher organisms. Statistics of rare events and “intelligent design”. Heredity of the characters acquired during epigenesis: Darwin and Lamarck. Structure of the brain and human mind: the role of genetic inheritance and the one of the ambient and of the experiences in the formation and evolution of the mind and personality. Arbitrarity and redundancy in the evolution of  living organisms and that of human languages.
Keywords: Biological evolution and cultural evolution; adaptive mutation; inheritance of epigenetically acquired characters; brain and mind; human person and time; evolution of human languages and biological evolution.